A Note on the history of Hellenistic Megara: Τhe date of the Antigonid garrison in Aegosthena - Chrysafis, Charalampos (Tekmeria, 2019)
This paper presents a proposal for the date of the Antigonid military presence in Aegosthena near Megara, which is known only by a Megarian honorary decree for Boiotian Zoilos, the royal commander of the garrison (IG VII 1). The named king Demetrios in the inscription could be Poliorketes (306-284 BC) or his grandson, Demetrios II (239-229 BC). All the available evidences (philological, prosopographical, letters a.o.) are examined and the conclusion is that a date around 295-287 BC is the more preferable.